Photocatalyst for CO2 reduction and preparation method and application thereof
By interspersing carbon nanotubes into the shell of Cu2O hollow nanospheres in a photocatalyst, the problem of low reaction activity and poor selectivity of the photocatalyst during CO2 reduction is solved, and efficient photocatalytic CO2 conversion is achieved.
Patent Information
- Application Number
- CN202411483979.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-23
- Publication Date
- 2025-03-11
AI Technical Summary
The existing photocatalysts have low reaction activity and poor selectivity during CO2 reduction, and the photogenerated charge migration efficiency is low, resulting in low overall reaction efficiency.
Using a photocatalyst composed of Cu2O hollow nanospheres and acid-deficient carbon nanotubes, the carbon nanotubes are dispersed in the shell of Cu2O hollow nanospheres in interspersed form to form an effective electron migration channel.
The migration ability and separation efficiency of photogenerated charges have been significantly improved, the photocatalytic activity and stability have been improved, and the CO yield has reached 60.25μmol g-1h-1, with a selectivity of nearly 100%.
Smart Images

Figure CN119588351A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of catalysts, and in particular to a photocatalyst for CO2 reduction and a preparation method and application thereof. Background Art
[0002] Currently, photocatalytic CO2 reduction technology has attracted much attention due to its potential in addressing global energy and environmental challenges. Photocatalysts can use solar energy to convert CO2 and water into valuable fuels, providing a sustainable solution to energy shortages and greenhouse gas emissions. During the photocatalytic reaction, photogenerated electrons and holes are generated inside the semiconductor material, but their migration to the surface active sites is often hindered, which greatly reduces the photocatalytic efficiency. Therefore, the main challenge to achieving efficient photocatalysis is to solve the migration problem of photogenerated charges. To address this challenge, researchers usually add sacrificial agents and other reaction additives to the reaction to help improve the catalytic efficiency. However, under additive-free test conditions, the activity of existing photocatalysts is generally low. For example, the CO product rate corresponding to the commercial P25 photocatalyst is less than 1 μmol g -1 h -1 Without additional additives to enhance the reaction, limited charge separation and slow electron migration would further inhibit the overall reaction efficiency.
[0003] Therefore, there is an urgent need to provide a photocatalyst with excellent charge separation efficiency for achieving efficient photocatalytic CO2 conversion.
[0004] In recent years, scientists have used the excellent conductive properties of carbon nanotubes to enhance the photoelectric properties of photocatalysts and thus improve photocatalytic activity. However, existing technologies only load carbon nanotubes onto the surface of catalyst carriers. Since photogenerated electrons are generated in the entire structure of the photocatalyst, in photocatalysts loaded with carbon nanotubes on the surface, the internal photogenerated electrons are still difficult to migrate to the surface, and the carbon nanotubes on the surface have limited effect in enhancing the photogenerated electrons. Summary of the invention
[0005] The purpose of the present invention is to overcome the problems of low reaction activity and poor selectivity of the photocatalyst in the prior art when used for CO2 reduction.
[0006] In order to achieve the above-mentioned object, the first aspect of the present invention provides a photocatalyst for CO2 reduction, the photocatalyst comprising Cu2O hollow nanospheres and carbon nanotubes, wherein the carbon nanotubes are dispersed in the shell layer of the Cu2O hollow nanospheres in an interlaced form;
[0007] The specific surface area of the photocatalyst is 15-35m 2 g -1 , pore volume is 0.09-0.4cm 3 g-1 , the average pore size is 7-13nm.
[0008] The second aspect of the present invention provides a method for preparing the photocatalyst according to the first aspect, the method comprising:
[0009] (1) in the presence of a solvent, bringing copper acetate into first contact with polyvinyl pyrrolidone to obtain a first material;
[0010] (2) contacting the carbon nanotubes with the first material for a second time to obtain a second material; the carbon nanotubes are acid-deficient carbon nanotubes;
[0011] (3) contacting ascorbic acid with the second material for a third time to obtain the photocatalyst; the conditions of the third contact include: a temperature of 40-60° C. and a time of 2-4 hours;
[0012] The mass ratio of the carbon nanotubes, the copper acetate, the polyvinyl pyrrolidone and the ascorbic acid is 1:20-30:6.5-9.5:10-14.
[0013] The third aspect of the present invention provides a photocatalyst prepared by the method described in the second aspect.
[0014] The fourth aspect of the present invention provides the use of the photocatalyst described in the first aspect and the second aspect in CO2 reduction.
[0015] The photocatalyst provided by the present invention has a structure in which carbon nanotubes are dispersed in the shell layer of the Cu2O hollow nanospheres in an interlaced form, the carbon nanotubes connect the interior and surface of the Cu2O nanospheres, and there is effective contact on the surface and interior of the photocatalyst. This structure promotes the transfer of internal photogenerated electrons, and serves as a high-speed electron migration channel to quickly transfer the photogenerated electrons to the surface, greatly improving the migration ability and separation efficiency of the photogenerated charges in the Cu2O catalyst, and also greatly improving the photocatalytic activity and stability. BRIEF DESCRIPTION OF THE DRAWINGS
[0016] Figure 1 is a morphological characterization diagram of the photocatalyst obtained in Example 1 provided by the present invention;
[0017] Figure 2 This is a comparison chart of the photoelectric performance of the photocatalyst obtained in Example 1 and the Cu2O nanospheres obtained in Comparative Example 1 provided by the present invention;
[0018] Figure 3 This is a photocatalytic stability test diagram of the photocatalyst of Example 1 provided by the present invention;
[0019] Figure 4It is an infrared spectrum of the photocatalyst obtained in Example 1, the Cu2O nanospheres obtained in Comparative Example 1, and the carbon nanotubes A obtained in Preparation Example 1 provided by the exemplary embodiment of the present invention;
[0020] Figure 5 It is the XRD diagram of the photocatalyst obtained in Example 1 and the Cu2O nanospheres obtained in Comparative Example 1 provided by way of example of the present invention. DETAILED DESCRIPTION
[0021] The endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.
[0022] As mentioned above, the first aspect of the present invention provides a photocatalyst for CO2 reduction, the photocatalyst comprising Cu2O hollow nanospheres and carbon nanotubes, wherein the carbon nanotubes are dispersed in the shell of the Cu2O hollow nanospheres in an interlaced form;
[0023] The specific surface area of the photocatalyst is 15-35m 2 g -1 , pore volume is 0.09-0.4cm 3 g -1 , the average pore size is 7-13nm.
[0024] Preferably, the specific surface area is 23-35m 2 g -1 , pore volume is 0.12-0.4cm 3 g -1 , the average pore size is 7-13nm.
[0025] More preferably, the specific surface area is 29-31m 2 g -1 , pore volume is 0.2-0.3cm 3 g -1 , the average pore size is 8-10nm.
[0026] Preferably, the average particle diameter of the photocatalyst is 800-1000 nm, preferably 800-900 nm.
[0027] As mentioned above, the second aspect of the present invention provides a method for preparing the photocatalyst described in the first aspect, the method comprising:
[0028] (1) in the presence of a solvent, bringing copper acetate into first contact with polyvinyl pyrrolidone to obtain a first material;
[0029] (2) contacting the carbon nanotubes with the first material for a second time to obtain a second material; the carbon nanotubes are acid-deficient carbon nanotubes;
[0030] (3) contacting ascorbic acid with the second material for a third time to obtain the photocatalyst; the conditions of the third contact include: a temperature of 40-60° C. and a time of 2-4 hours;
[0031] The mass ratio of the carbon nanotubes, the copper acetate, the polyvinyl pyrrolidone and the ascorbic acid is 1:20-30:6.5-9.5:10-14.
[0032] Preferably, the conditions of the third contact include: a temperature of 45-55° C. and a time of 2.5-3.5 hours. The inventors found that under this preferred embodiment, the photocatalyst obtained by the present invention has better catalytic activity and stability.
[0033] Preferably, the third contact is carried out under stirring conditions, and the stirring speed is 100-200 rpm.
[0034] More preferably, the mass ratio of the carbon nanotubes, the copper acetate, the polyvinyl pyrrolidone and the ascorbic acid is 1:24-26:7.5-8.5:12-13. The inventors found that under this preferred embodiment, the photocatalyst obtained by the present invention has better catalytic activity and stability.
[0035] Preferably, in step (1), the method further comprises: first contacting the copper acetate aqueous solution with the polyvinyl pyrrolidone aqueous solution to obtain a first material; the concentration of the copper acetate aqueous solution is 0.03-0.05 g / mL, and the concentration of the polyvinyl pyrrolidone aqueous solution is 0.01-0.03 g / mL.
[0036] More preferably, the conditions of the first contact reaction include: temperature of 20-25°C, time of 30-40 min, and stirring speed of 200-500 rpm.
[0037] Preferably, in step (2), the method further comprises preparing the carbon nanotubes by a method comprising the following steps: reacting carbon nanotubes I with nitric acid having a concentration of 65-70wt% to obtain the carbon nanotubes; the reaction conditions comprising: a temperature of 80-90°C and a reaction time of 4.5-5.5h.
[0038] Preferably, the amount of the carbon nanotubes I used is 0.1-0.3 g relative to 100 mL of 65-70 wt % nitric acid.
[0039] More preferably, the carbon nanotubes I have an average length of 0.8-1.2 μm and an average diameter of 10-30 nm. The inventors found that under this preferred embodiment, the photocatalyst obtained by the present invention has better catalytic activity and stability.
[0040] Further preferably, in step (2), the method further comprises preparing the carbon nanotubes by a method comprising the following steps: reacting carbon nanotubes I with nitric acid having a concentration of 65-70wt%, washing the product alternately with water and ethanol for 3-8 times, and then drying the product to obtain the carbon nanotubes; the conditions for the drying treatment include: a temperature of 65-75°C and a time of 10-14h.
[0041] In order to obtain an interpenetrating photocatalyst, preferably, in the initial system where the carbon nanotubes are in second contact with the first material, the carbon nanotubes are dispersed in N,N-dimethylacetamide; the concentration of the carbon nanotubes is 4-6 mg / mL; and the dispersion conditions include: an ultrasonic frequency of 80-100 kHz and a time of 3-4 h.
[0042] Preferably, in step (2), the conditions for the second contact include: temperature of 20-25° C., time of 30-40 min, and stirring speed of 100-300 rpm.
[0043] Preferably, in step (3), in the initial system for the third contact, the ascorbic acid is an ascorbic acid aqueous solution with a concentration of 0.018-0.02 g / mL.
[0044] Preferably, in step (3), the method further comprises: the ascorbic acid is brought into a third contact with the second material in a dripping manner; the dripping speed is 0.2-0.5 mL / s.
[0045] More preferably, in the initial system where the ascorbic acid and the second material are brought into contact with each other for the third time, the temperature of the second material is not less than 30°C.
[0046] Preferably, in step (3), the method further comprises: bringing ascorbic acid into a third contact with the second material, washing the obtained product with water and ethanol for 3-5 times in sequence, and then drying at 45-55° C. for 8-12 hours to obtain the photocatalyst.
[0047] As mentioned above, the third aspect of the present invention provides a photocatalyst prepared by the method described in the second aspect.
[0048] As mentioned above, the fourth aspect of the present invention provides the use of the photocatalyst described in the first and third aspects in CO2 reduction.
[0049] The present invention will be described in detail below by way of examples. Unless otherwise specified, the instruments and reagents used in the following examples are all commercially available, and the reagents are all analytically pure.
[0050] Preparation Example 1
[0051] This preparation example is used to illustrate that the carbon nanotubes provided by the present invention are subjected to acid defect treatment according to the following steps:
[0052] 0.1 g of carbon nanotubes I and 50 mL of 70 wt % nitric acid were heated under reflux in an oil bath at 90° C. for 5 h. The obtained product was washed alternately with water and ethanol for 5 times and then dried at 70° C. for 12 h to obtain the carbon nanotubes A (CNTs).
[0053] The carbon nanotubes I have an average length of 1 μm and an average diameter of 20 nm.
[0054] Preparation Example 2
[0055] The process is similar to that of Preparation Example 1, except that the average length of the carbon nanotubes I is 3 μm and the average diameter is 40 nm.
[0056] The rest is the same as Preparation Example 1.
[0057] Carbon nanotubes B are prepared.
[0058] Example 1
[0059] Copper acetate aqueous solution: concentration 0.042 g / mL;
[0060] Polyvinyl pyrrolidone aqueous solution: concentration 0.02 g / mL;
[0061] Ascorbic acid aqueous solution: concentration 0.02 g / mL;
[0062] N,N-dimethylacetamide solution of carbon nanotubes A: carbon nanotubes A are dispersed in N,N-dimethylacetamide, and the dispersion conditions include: ultrasonic frequency of 100 kHz, time of 4 hours, and a solution with a concentration of 5 mg / mL is obtained;
[0063] (1) contacting a copper acetate aqueous solution with a polyvinyl pyrrolidone aqueous solution to obtain a first material; the conditions of the first contact reaction are: temperature of 20° C., time of 30 min, and stirring speed of 300 rpm;
[0064] (2) contacting the N,N-dimethylacetamide solution of carbon nanotubes A with the first material for a second time to obtain a second material; the conditions of the second contact are: temperature of 20° C., time of 30 min, and stirring speed of 150 rpm;
[0065] (3) The second material is heated to 30° C., and then an ascorbic acid aqueous solution is added dropwise (at a dropping speed of 0.3 mL / s) to the second material for a third contact. The resulting product is washed three times with water and ethanol in sequence, and then dried at 50° C. for 10 h to obtain the photocatalyst S1 (Cu2O-Vo-CNTs); the conditions for the third contact are: temperature of 50° C., time of 3 h, and stirring speed of 150 rpm;
[0066] Based on dry weight, the mass ratio of the carbon nanotube A, the copper acetate, the polyvinyl pyrrolidone and the ascorbic acid is 1:25.2:8:12;
[0067] The specific surface area of the photocatalyst S1 is 30 m 2 g -1 , pore volume is 0.25cm 3 g -1 , the average pore size is 9nm;
[0068] The average particle diameter of the photocatalyst S1 is 900 nm.
[0069] The present invention also exemplarily provides the morphological characterization analysis of the photocatalyst prepared in Example 1; Figure 1 As shown, from Figure 1 It can be seen that carbon nanotubes are interspersed in the Cu2O nanosphere shell layer, and Cu2O presents a hollow nanosphere structure.
[0070] Example 2
[0071] Copper acetate aqueous solution: concentration 0.05 g / mL;
[0072] Polyvinyl pyrrolidone aqueous solution: concentration 0.01 g / mL;
[0073] Ascorbic acid aqueous solution: concentration 0.018 g / mL;
[0074] Carbon nanotube A in N,N-dimethylacetamide solution: concentration 6 mg / mL;
[0075] (1) contacting a copper acetate aqueous solution with a polyvinyl pyrrolidone aqueous solution to obtain a first material; the conditions of the first contact reaction are: temperature of 20° C., time of 30 min, and stirring speed of 300 rpm;
[0076] (2) contacting the N,N-dimethylacetamide solution of carbon nanotubes A with the first material for a second time to obtain a second material; the conditions for the second contact are: temperature of 20° C., time of 30 min, and stirring speed of 300 rpm;
[0077] (3) The second material is heated to 30° C., and then an ascorbic acid aqueous solution is added dropwise (at a dropping speed of 0.3 mL / s) to the second material for a third contact. The resulting product is washed three times with water and ethanol in sequence, and then dried at 50° C. for 10 h to obtain the photocatalyst S2. The conditions for the third contact are: temperature of 45° C., time of 3.5 h, and stirring speed of 100 rpm.
[0078] Based on dry weight, the mass ratio of the carbon nanotubes A, the copper acetate, the polyvinyl pyrrolidone and the ascorbic acid is 1:26:7.5:12.5.
[0079] The specific surface area of the photocatalyst S2 is 30 m 2 g -1 , pore volume is 0.24 cm 3 g -1 , the average pore size is 9nm.
[0080] Example 3
[0081] This example is carried out using a process similar to that of Example 1, except that this example uses carbon nanotubes B prepared in Preparation Example 2 of equal mass to replace carbon nanotubes A in Example 1.
[0082] The rest are the same as in Example 1.
[0083] Photocatalyst S3 was prepared.
[0084] The specific surface area of the photocatalyst S3 is 25 m 2 g -1 , pore volume is 0.15 cm 3 g -1 , the average pore size is 13nm.
[0085] Example 4
[0086] This example is carried out using a process similar to that of Example 1, except that, in this example, based on dry weight, the mass ratio of the carbon nanotubes A, the copper acetate, the polyvinyl pyrrolidone and the ascorbic acid is 1:25.2:8:15.
[0087] The rest are the same as in Example 1.
[0088] Photocatalyst S4 was prepared.
[0089] The specific surface area of the photocatalyst S4 is 23 m 2 g -1 , pore volume is 0.12 cm 3 g -1 , the average pore size is 11nm.
[0090] Example 5
[0091] This example is carried out using a process similar to that of Example 1, except that, in this example, the mass ratio of the carbon nanotubes A, the copper acetate, the polyvinyl pyrrolidone and the ascorbic acid is 1:15:10:12 on a dry weight basis.
[0092] The rest are the same as in Example 1.
[0093] Photocatalyst S5 was prepared.
[0094] The specific surface area of the photocatalyst S5 is 15 m 2 g -1 , pore volume is 0.09 cm 3 g -1 , the average pore size is 11nm.
[0095] Example 6
[0096] This embodiment adopts a process similar to that of Embodiment 1, except that in this embodiment, the temperature of the third contact is 60°C.
[0097] The rest are the same as in Example 1.
[0098] Photocatalyst S6 was prepared.
[0099] The specific surface area of the photocatalyst S6 is 16 m 2 g -1 , pore volume is 0.09 cm 3 g -1 , the average pore size is 11nm.
[0100] Example 7
[0101] The raw materials and proportions used in this embodiment are the same as those in the embodiment, except that this embodiment adopts a one-step mixing method, specifically:
[0102] (1) A copper acetate aqueous solution, a polyvinyl pyrrolidone aqueous solution, an N,N-dimethylacetamide solution of carbon nanotube A and an ascorbic acid aqueous solution are mixed and reacted, and the resulting product is washed with water and ethanol three times in sequence, and then dried at 50°C for 10 hours to obtain the photocatalyst S7; the conditions of the mixed reaction are: temperature of 50°C, time of 3 hours, and stirring speed of 150 rpm.
[0103] The specific surface area of the photocatalyst S7 is 25 m 2 g -1 , pore volume is 0.15 cm 3 g -1, the average pore size is 13nm.
[0104] Comparative Example 1
[0105] The catalyst used in this comparative example is Cu2O nanospheres, and the specific preparation steps are as follows:
[0106] Copper acetate aqueous solution: concentration 0.042 g / mL;
[0107] Polyvinyl pyrrolidone aqueous solution: concentration 0.02 g / mL;
[0108] Ascorbic acid aqueous solution: concentration 0.02 g / mL;
[0109] (1) contacting a copper acetate aqueous solution with a polyvinyl pyrrolidone aqueous solution to obtain a first material; the conditions of the first contact reaction are: temperature of 20° C., time of 30 min, and stirring speed of 300 rpm;
[0110] (3) dropping an ascorbic acid aqueous solution (dropping speed of 0.3 mL / s) into the first material to react, washing the obtained product with water and ethanol three times in sequence, and then drying at 50° C. for 10 h to obtain the Cu2O nanospheres; the conditions of the first reaction are: temperature of 50° C., time of 3 h, and stirring speed of 150 rpm;
[0111] Based on dry weight, the mass ratio of the copper acetate, the polyvinyl pyrrolidone and the ascorbic acid is 25.2:8:12.
[0112] Comparative Example 2
[0113] The comparative example is a commercial catalyst P25 (manufacturer: MacLean Reagent, model: T818939-25g).
[0114] Test Example 1
[0115] This test example tests the catalytic performance of the photocatalyst of the above example for photocatalytic CO2.
[0116] Weigh 20 mg of the photocatalyst prepared in the above example, mix it with 2.0 ml of deionized water in a watch glass with a diameter of 6.0 cm, and ultrasonicate for 5 minutes to form a uniform suspension. The watch glass containing the suspension is placed horizontally in a Platinum Philae 6A reactor for photocatalytic reaction. In order to eliminate the influence of impurities, the reactor is filled and evacuated with 80 KPa of carbon dioxide gas and treated 3 times. The chromatographic cycle is set to inject the gas after the photocatalytic reaction once every 0.5 h, for a total of 8 times. The FID 1 channel records the content of CO and CH4 after each injection, and the TCD channel records the content of O2 and H2. The results are shown in Table 1.
[0117] Table 1
[0118]
[0119]
[0120] Note: In Table 1, a is the reaction conditions: catalyst sample is 0.02 g; water is 2 mL; CO2 pressure is 80 MPa; irradiation time is 4 h, reaction temperature is 5 ° C; b is product selectivity (%) = n (CO) or n (CH4) / [n (CO) + n (CH4)] × 100%.
[0121] From the results in Table 1, it can be seen that the photocatalyst provided by the present invention has better catalytic activity. In particular, when the photocatalyst obtained in Example 1 is used for the reduction of CO2, the CO yield is as high as 60.25 μmol g -1 h -1 The selectivity is 99.62%, almost 100%. When the optimized photocatalyst of the present invention is used for the reduction of CO2, the CO yield is 8 times that of pure Cu2O nanospheres and 87 times that of traditional P25 photocatalysts.
[0122] In order to further illustrate the catalytic performance of the photocatalyst provided by the present invention, the present invention also exemplarily provides the photoelectric performance of the photocatalyst ((Cu2O-Vo-CNTs)) provided in Example 1 of the present invention and the Cu2O nanospheres provided in Comparative Example 1, such as Figure 2 As shown, the results of electrochemical impedance, transient photocurrent and photoluminescence fluorescence spectrum of Cu2O nanospheres and the photocatalyst (Cu2O-Vo-CNTs) provided by the present invention are compared, which unanimously shows that the photocatalyst provided by the present invention greatly improves the electron migration ability and charge separation efficiency of the original Cu2O nanospheres.
[0123] In order to further illustrate the stability of the photocatalyst provided by the present invention, the present invention also exemplarily provides the photocatalytic stability of the photocatalyst of Example 1 of the present invention, such as Figure 3 As shown, the photocatalyst of Example 1 was subjected to a photocatalytic reduction test and repeated for 5 cycles. After 5 cycles of activity test experiments, the CO yield of the photocatalyst remained basically unchanged in each cycle test, which shows that the photocatalyst prepared by the present invention has good photocatalytic stability.
[0124] Furthermore, the present invention also provides, by way of example, infrared and XRD characterizations of the carbon nanotubes A (CNTs) of Preparation Example 1, the photocatalyst S1 (Cu2O-Vo-CNTs) prepared in Example 1, and the Cu2O nanospheres prepared in Comparative Example 1, such as Figure 4 and Figure 5 As shown, from Figure 4It can be seen from the infrared characterization that CNTs have a -1 There is an obvious infrared peak at 629cm, which is caused by the stretching vibration of the C=C bond at the defect in the carbon skeleton, while the Cu2O nanosphere sample has an infrared peak at 629cm -1 The infrared peak at corresponds to the information of Cu-O bond. The infrared information of defective carbon nanotubes and Cu2O was found simultaneously in the Cu2O-Vo-CNTs sample, indicating the successful coupling of surface CNTs and Cu2O carrier.
[0125] from Figure 5 It can be seen from the XRD that the XRD diffraction peaks of the Cu2O nanosphere catalyst correspond to the PDF card of Cu2O, and the surface Cu2O nanospheres show a Cu2O crystal structure. After the addition of CNTs, the phase structure of Cu2O did not change significantly, indicating that the addition of CNTs did not destroy the phase structure of the catalyst base. The weak diffraction signal and low content of CNTs themselves resulted in no XRD diffraction peaks of CNTs in the Cu2O-Vo-CNTs sample.
[0126] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.
Claims
1. A photocatalyst for CO2 reduction, characterized in that: The photocatalyst comprises Cu2O hollow nanospheres and carbon nanotubes, wherein the carbon nanotubes are dispersed in the shell layer of the Cu2O hollow nanospheres in an interlaced manner; The specific surface area of the photocatalyst is 15-35m 2 g -1 , pore volume is 0.09-0.4cm 3 g -1 , the average pore size is 7-13nm; Preferably, the specific surface area is 23-35m 2 g -1 , pore volume is 0.12-0.4cm 3 g -1 , the average pore size is 7-13nm; More preferably, the specific surface area is 29-31m 2 g -1 , pore volume is 0.2-0.3cm 3 g -1 , the average pore size is 8-10nm.
2. The photocatalyst according to claim 1, characterized in that: The average particle diameter of the photocatalyst is 800-1000 nm, preferably 800-900 nm.
3. A method for preparing the photocatalyst according to claim 1 or 2, characterized in that: The method includes: (1) in the presence of a solvent, bringing copper acetate into first contact with polyvinyl pyrrolidone to obtain a first material; (2) contacting the carbon nanotubes with the first material for a second time to obtain a second material; the carbon nanotubes are acid-deficient carbon nanotubes; (3) contacting ascorbic acid with the second material for a third time to obtain the photocatalyst; the conditions of the third contact include: a temperature of 40-60° C. and a time of 2-4 hours; The mass ratio of the carbon nanotubes, the copper acetate, the polyvinyl pyrrolidone and the ascorbic acid is 1:20-30:6.5-9.5:10-14.
4. The method according to claim 3, characterized in that The conditions of the third contact include: temperature of 45-55° C. and time of 2.5-3.5 h.
5. The method according to claim 3 or 4, characterized in that: The mass ratio of the carbon nanotubes, the copper acetate, the polyvinyl pyrrolidone and the ascorbic acid is 1:24-26:7.5-8.5:12-13.
6. The method according to any one of claims 3 to 5, characterized in that: In step (1), the method further comprises: first contacting a copper acetate aqueous solution with a polyvinyl pyrrolidone aqueous solution to obtain a first material; the concentration of the copper acetate aqueous solution is 0.03-0.05 g / mL, and the concentration of the polyvinyl pyrrolidone aqueous solution is 0.01-0.03 g / mL; Preferably, the conditions of the first contact reaction include: temperature of 15-25°C, time of 30-40 min, and stirring speed of 200-500 rpm.
7. The method according to any one of claims 3 to 6, characterized in that: In step (2), the method further comprises preparing the carbon nanotubes by a method comprising the following steps: reacting the carbon nanotubes I with nitric acid having a concentration of 65-70 wt % to obtain the carbon nanotubes; The reaction conditions include: temperature of 80-90°C and time of 4.5-5.5h; Preferably, the carbon nanotubes I have an average length of 0.8-1.2 μm and an average diameter of 10-30 nm.
8. The method according to any one of claims 3 to 7, characterized in that: In step (2), the conditions of the second contact include: temperature of 15-25°C, time of 30-40 min, stirring speed of 100-300 rpm; And / or, in step (3), the method further comprises: the ascorbic acid is brought into a third contact with the second material in a dropwise manner; the dropwise addition speed is 0.2-0.5 mL / s; Preferably, in the initial system where the ascorbic acid and the second material are brought into third contact, the temperature of the second material is not less than 30°C.
9. A photocatalyst prepared by the method according to any one of claims 3 to 8.
10. Use of the photocatalyst described in claims 1, 2 and 9 in CO2 reduction.